Three-dimensional crisscross porous manganese oxide/carbon composite networks for high performance supercapacitor electrodes. (10th April 2015) - Li, Chunying; Wang, Shuyuan; Zhang, Guowei; Du, Zhiling; Wang, Guiling; Yang, Jing; Qin, Xiujuan; Shao, Guangjie
Highlights: Three-dimensional inter-connected porous networks of manganese oxide/carbon composites were successfully developed. The powdery composite possesses good conductivity and favorable porosity. The composite electrode delivers an outstanding specific capacitance of 807 F g −1 at 1 A g −1 . Abstract: Manganese oxide/carbon (MnO x /C) composites have been successfully prepared via a high temperature heat treatment method followed by the electrochemical oxidation. The presence of carbon not only enhances the electronic conductivity of manganese oxides (MnO x ), but also provides more active sites for the transformation of manganese monoxide (MnO) during the galvanostatic charge–discharge process. Simultaneity, the interconnected porous structures of MnO x /C samples are believed to provide a continuous channel for the diffusion of electrolyte ion and shorten the diffusion length of ions involved in the charge/discharge cycling processes. Consequently, these advantages endow the MnO x /C electrode a better capacitance performance, a superior long-term cyclic stability and outstanding rate capability compared with pristine MnO x . More importantly, the composites show a fascinating capacitance of 807 F g −1 at 1 A g −1, which is much higher than the reported hydrous RuO2 electrodes. It can be easily speculated that MnO x /C composites will act as a promising electrode materials for designing high-performance supercapacitors.